The journal of curious letters / 1. - Dashner, James., 1972- (13th reality, 2008)
Thirteen-year-old Atticus "Tick" Higginbottom begins receiving mysterious letters from around the world signed only "M.G.," and the clues contained therein lead him on a journey to the perilous 13th Reality and a confrontation with evil Mistress Jane.